Neuroprotective Effects of Casein-Derived Peptide Met-Lys-Pro (MKP) in a Hypertensive Model - Tada, Asuka Matsuzaki; Hamezah, Hamizah Shahirah; Yanagisawa, Daijiro; Morikawa, Shigehiro; Tooyama, Ikuo (Frontiers in Neuroscience, 2020)
We have previously reported that casein hydrolysate, CH-3, from bovine milk and casein-derived tripeptide Met-Lys-Pro (MKP) has ACE inhibitory activity and reduces blood pressure. In this study, we investigated the therapeutic effects of MKP in a hypertensive rat model (7-week-old male SHRSP/Izm rats). For long term evaluation, rats were fed either a diet containing CH-3 or normal diet. The survival rate of SHRSP rats was significantly improved by intake of CH-3 for 181 days. For short term evaluation, rats were orally administered synthetic tripeptide MKP or distilled water for 4 weeks. MRI study demonstrated that hemorrhagic lesions were observed in two of five rats in the control group, while no hemorrhagic lesions were observed in the MKP group. Volumetric analysis using MRI revealed that MKP administration inhibited atrophy of diencephalic regions. Histological examinations revealed that hemorrhage areas and astrogliosis in the hippocampus and cerebral cortex were lower in the MKP group than in the control group. Gene expression analysis indicated that MKP administration reduced expression of genes related to cerebral circulation insufficiency such as immune responses (Cd74 and Prkcd), response to hypoxia (Ddit4, Apold1, and Prkcd), reactive oxygen species metabolic process (Ddit4 and Pdk4), and apoptotic process (Ddit4, Prkcd, and Sgk1), suggesting that MKP administration prevented cerebral ischemia associated with hypertension. In addition, some genes encoding responses to hormone stimulus (Fos, Dusp1, and Sik1) were also downregulated. Serum aldosterone and corticosterone levels were also significantly decreased following MKP administration. The present study indicates that MKP shows neuroprotective effects in SHRSP rats by regulating cerebral circulation insufficiency and corticoid levels. MKP administration may therefore be a potential therapeutic strategy for hypertensive brain diseases such as cerebrovascular disease.